AN INVESTIGATION ON THE ABILITY OF SECOND YEAR STUDENTS OF SMAN 2 PEKANBARU IN USING QUESTION TAGS THROUGH DRAMA SCRIPT - Eldiyanto, Arif Eldiyanto; Azhar, Fadly Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Â Abstract: The purpose of this study is to find students ability of SMAN 2 Pekanbaru in using question tags. This research focuses in grammar, especially for question tag in simple present tense with âbeâ, simple past tense with âbeâ, simple present tense with verb, simple past tense with verb, and modal auxiliaries.The instrument used by the writer to collect the data for this study isdrama script and full of incomplete dialogues. Try out was conducted to check validity and reliability of the test. There were 31 students as samples from XI science 1 of the second year students of SMAN 2 Pekanbaru. Based on the research finding, it can be found: first, the ability of the students in using question tags is infair ability level.Second, the studentsâ scores in using question tags in simple present tense with âbeâ is 57,5, simple past tense with âbeâ is 66,1 , simple present tense with verb is 57,5, simple past tense with verb is 67,1, and modal auxiliaries is 58,6. As a result,the highest score obtained by the students in identifying question tags in simple past with âverbâ. It is 67,1 that falls into fair ability level, andthe lowest score that the students get is in identifying question tags in simple present tense with âverbâ. It is 57,5 which falls into poor ability level. Â Keywords:Ability, Using, Question tags.